Continuous Fields with Fibres O_∞ - Blanchard, Etienne (MATHEMATICA SCANDINAVICA, 2014)
We study in this article a class of unital continuous C^*-bundles the fibres of which are all isomorphic to the Cuntz C^*-algebra O_∞. This enables us to give several equivalent reformulations for the triviality of all these C^*-bundles.